Makna Simbolis Sumbang Duo Baleh dalam Seni Pertunjukan Wanita Minangkabau - Fuji Astuti (Fakultas Bahasa dan Seni UNP, 2011)
The limitation of women’s opportunities in the activities of the performing arts in the past were opportunities associated with the regulation norms in the foundations of Minangkabau customs. Within the social order, Minangkabau custom placed a woman as a person having the autonomy known as Bundo Kanduang, a perfect woman that should be the model for her descendants, the light in the village, the one who can keep the beauty of the country. Because of this, the women’s participation was limited around Rumah Gadang. In Line with the development of the era, the improvement on formal and non-formal education makes the Minangkabau women aware their limitation to participate in the world of performance arts. Nowadays there is a great opportunity for the women to determine their own choices in the performance arts. This opportunity has resulted in the more dominant presence of woman in the Minangkabau performing arts. Particularly in the world of dancing, the initiators of dance creation art have produced the dances with both the masculine and feminine moves which can be performed by Minangkabau women in the world of performing arts. The most interesting thing is there is a widely open opportunity for the women make their own choices. However, all the movements and behaviors of the Minangkabau women should be based on the social norms that are set in the philosophy of sumbang duo baleh and Alua jo patuik Raso jo pareso. Raso dibao naiak, pareso dibawo turun. Keywords: symbolic meaning, sumbang duo baleh, performing arts